(untitled) (Research, Society and Development, 2021)
The year 2020 was an atypical year in several segments, this year we need to change habits, isolate ourselves to contain the progress of the COVID-19 pandemic, at that moment we had to relearn how to live, and with that cultural aspects around the world were somehow affected, what seemed so far from reality has become the best alternative for the economy, digital has been included in our daily lives, the electronic commerce sector that grew 12% in the first half of 2019, had a record of growth in the same period analyzed in the year 2020. In this work we will address how e-commerce was impacted by the pandemic, and what are the expectations for the coming years. The research was developed in a bibliographic and quantitative way, combining theory with data obtained from data collected from the latest information available through the EBIT / Nielsen award. We will compare the growth and analyze the client’s profile, using databases from the last published editions. In this work, the objective was to address the decision-making behavior of millennials, as this is the biggest player in the sport.